2022
DOI: 10.1111/ijac.14004
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐derived sodium silicate for the manufacture of alkali‐activated binders: Use of bamboo leaf ash as silicate source

Abstract: Alkali activated binders are a promising alternative to the use of Portland cement in the manufacture of concrete for curbing CO2 emissions. Novel sources of silicates have been investigated in recent years for reducing cost and environmental impacts associated with the use of chemical activators. This study describes the production of solid sodium silicate (SS) activating powder from bamboo leaf ash (BLA). Bamboo leaves were calcined at 550–800°C, mixed with NaOH pellets, and heated in an oven at 300°C. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…In addition, the majority of studies used commercially available activators. No studies reported on the acid resistance of AABs prepared with novel low-carbon activators, such as those developed using rice husk ash, bamboo leaf or waste glass [11][12][13]. The effect of the curing regime on acid resistance was also rarely considered.…”
Section: Performance Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the majority of studies used commercially available activators. No studies reported on the acid resistance of AABs prepared with novel low-carbon activators, such as those developed using rice husk ash, bamboo leaf or waste glass [11][12][13]. The effect of the curing regime on acid resistance was also rarely considered.…”
Section: Performance Summarymentioning
confidence: 99%
“…The most commonly used activators are alkali hydroxide or silicate solutions (usually Na or K) [8]. Unfortunately, the alkaline activators generally have a much greater environmental footprint than the aluminosilicate source materials, which has resulted in a search for alternative low-carbon activators to enhance the environmental credentials of AABs further [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…WG-based activator gave lower early strength (1-day) but equal or superior 7 and 28-day strengths than the commercially available activating solutions. Since the method was proposed, it has been replicated and verified by several researchers (see, e.g., [16]), using other silicate sources (e.g., [17,18]), and providing environmental analysis confirming a potential for a 70% reduction in CO 2 emissions when compared to Portland cement-based concrete [19,20]. However, a detailed investigation of the microstructure of the reaction products when a WG-based activator is used has not been carried out yet.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have focused on the synthesis of this activator [13,14] using different silica-rich sources as raw materials. These sources include low-value, silicate-rich wastes [15][16][17][18], and bio-derived materials [19,20]. There are two main routes of synthesis that can be applied [21], a thermochemical method and a hydrothermal method.…”
Section: Introductionmentioning
confidence: 99%
“…There are two main routes of synthesis that can be applied [21], a thermochemical method and a hydrothermal method. The thermochemical method consists of mixing the silica-rich powder with a sodium hydroxide powder using a temperature of 450-600 • C [14,19,21], and the hydrothermal method consists of dissolving the silica-rich materials in an alkaline solution at a temperature ≤ 100 • C [15][16][17][18]. Therefore, products produced using the hydrothermal method are liquid and require less energy for production [21].…”
Section: Introductionmentioning
confidence: 99%